A Survey on the Asheville Project as a Successful Model of Efficient Role of Pharmacist in the Management of Chronic Diseases and the Available Opportunities for Achieving the Same Results in Iranian Health Society - Kheiry Avarvand, Omid; Roshanzamiri, Soheil; Eslami, Kaveh (International Pharmacy Acta, 2018)
Introduction Launched in 1997 by the city of Asheville, North Carolina, the Asheville project was a breakthrough in showing the importance of pharmacist role in pharmacotherapy process and management of chronic diseases. With the pharmaceutical care based concept and emphasizing on medication therapy management idea, they were successful on their main hypothesis.it is clear that having a system similar to Asheville project could help Iranian health care system in many aspects and also improve the role of pharmacists in therapeutic process. Methods and Results We studied different aspects of Asheville project including their interventions, their understudied parameters, and their methods for completing the connections between patients, pharmacists and physicians and their system for follow-up patients. After this analysis we go through Iran’s health care system to find out our opportunities for designing an efficient MTM system according to our available resources. Asheville project focused on four type of most common chronic disease: diabetes, hypertension, asthma and hyperlipidemia. The common and always efficient intervention is patient education on self-management, for example in monitoring of blood sugar in diabetes and use of peak flow meter in asthma. Managing the polypharmacy and drug interactions, and consulting for referring to physicians in urgent situations was another intervention. After all , they got a big impact on improving clinical parameters like A1C, FEV1, HDL and LDL. They also experience reduction of the total health care costs and increase satisfaction with pharmacist services among patients. Their efficient follow-up system was the key of their successful experience. Conclusion Today in Iran we are facing the fast growing in the incidence of chronic diseases which demand an efficient system to follow-up patients and help them with different complications that they may experience.In addition to this facts, lowering the total cost of health care system and reducing the number of unnecessary clinical visits and clinical tests is important for economic aspects of our health care system. According to the successful experience of Asheville project and the current situation of chronic diseases in Iran, we can strongly suggest that working on MTM clinics and emphasizing on the role of pharmacist could help our system for managing this situation.